Uncovering the potential of cover cropping for regenerative horticulture - Smee, Matthew; Girkin, Nicholas T.; Simmons, Robert W.; Falagán, Natalia (Elsevier, 2026)
Cover cropping is increasingly promoted as a tool for enhancing sustainability and resilience in horticultural systems. This review synthesises the outcomes of 79 studies on cover cropping in temperate European horticulture, focusing on agronomic and ecological impacts. The evidence demonstrates that cover crops can improve yield and quality, enhance soil health indicators, increase nutrient density in follow on cash crops, suppress weeds, reduce synthetic chemical inputs, and improve nitrogen (N) availability. Tomato, cabbage, pepper, courgette, lettuce, baby leaf, and onion were the most frequently studied crops, with positive outcomes most consistently reported in yield, soil health, and nutrient density. However, outcomes were highly context-dependent, with negative effects, such as reduced yield, lower quality, increased weed pressure, or decreased N availability, occurring regularly. Conflicting results were influenced by species, composition, sowing dates, termination methods, crop type, and local agroecological conditions. For instance, legume cover crops increased N availability for some crops but led to N immobilisation or competition in others. Termination strategies also affected subsequent crop performance and soil health indicators. Farmer adoption remains limited, driven by perceived risks, management complexity, and knowledge gaps. Few studies examined ecological outcomes, multi-cropping strategies, or nutritional benefits, highlighting priorities for future research. This review demonstrates that cover cropping can be an important component of wider regenerative practices in horticulture, but success requires careful, site-specific management, iterative testing, and monitoring. Strategic integration of cover crops, informed by species selection, sowing and termination timing, and crop priorities, is essential to maximise benefits while minimising trade-offs.
Keywords: 30 Agricultural, Veterinary and Food Sciences; Generic health relevance; 2 Zero Hunger; Agronomy & Agriculture; 3002 Agriculture, land and farm management; 3004 Crop and pasture production; Climate change; Greenhouse gas emissions; Soil health; Nutrient cycling; Soil erosion